Proposal: different types of alteration and loss of consciousness in epilepsy - Lueders, Hans; Amina, Shahram; Bailey, Christopher; Baumgartner, Christoph; Benbadis, Selim; Bermeo, Adriana; Carreno, Maria; Devereaux, Michael; Diehl, Beate; Eccher, Matthew; Edwards, Jonathan; Fastenau, Philip; et al. (Epilepsia, 2014)
There are at least five types of alterations of consciousness that occur during epileptic seizures: auras with illusions or hallucinations, dyscognitive seizures, epileptic delirium, dialeptic seizures, and epileptic coma. Each of these types of alterations of consciousness has a specific semiology and a distinct pathophysiologic mechanism. In this proposal we emphasize the need to clearly define each of these alterations/loss of consciousness and to apply this terminology in semiologic descriptions and classifications of epileptic seizures. The proposal is a consensus opinion of experienced epileptologists, and it is hoped that it will lead to systematic studies that will allow a scientific characterization of the different types of alterations/loss of consciousness described in this article.
EVALuna2:22297